2006
DOI: 10.1007/s11365-006-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of desirability and feasibility on entrepreneurial intentions: A structural equation model

Abstract: There is general agreement that attitudes towards entrepreneurship are determinant factors to decide to be an entrepreneur. In this context, this research is focused on analyzing the relationship between desirability and feasibility on university student's intentions to create a new firm in Catalonia. A structural equation model supported by Krueger & Brazeal's Model was tested with different groups of students. The main results reveal most of university students consider desirable to create a new firm, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
285
4
26

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 393 publications
(345 citation statements)
references
References 33 publications
30
285
4
26
Order By: Relevance
“…Moreover, both variable, entrepreneurial motivation and entrepreneurial attitude found to be directly influence the entrepreneurial intention. This finding supports the works of Guerrero et al (2008), Fitzsimmons and Douglas (2005), Susetyo and Lestari (2014), Asmara et al (2016), Firmansyah et al (2016).…”
Section: Findings and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, both variable, entrepreneurial motivation and entrepreneurial attitude found to be directly influence the entrepreneurial intention. This finding supports the works of Guerrero et al (2008), Fitzsimmons and Douglas (2005), Susetyo and Lestari (2014), Asmara et al (2016), Firmansyah et al (2016).…”
Section: Findings and Discussionsupporting
confidence: 89%
“…Study conducted by Guerrero et al (2008) revealed that intrinsic motivation and normative environment have positive impact on entrepreneurial intentions. Likewise, personal capacity and regulatory environment have positive impact on the feasibility of starting new businesses.…”
Section: Introductionmentioning
confidence: 99%
“…He indentified that need for achievement and risk taking propensity are highly contributed for developing positive attitude toward entrepreneurship but the relationship between internal locus control and entrepreneurial attitude is not significant. Urbano (2008) investigated the impact of perceived desirability (social norms and attitude) and perceived feasibility (self-efficacy) on entrepreneurial intentions. Tong, Tong, Loy (2011) worked on only two personality traits including need for achievement and desire for independence.…”
Section: Relationship Between Entrepreneurial Intention and Various Dmentioning
confidence: 99%
“…Attitudes vary from one individual to another on factors influencing and, attractiveness of entrepreneurship as a career (Monitor, 2009). Guerrero et al (2008) found that attitudes towards entrepreneurship are determining factors to decide to be an entrepreneur. The perspectives and believes of students attitude toward entrepreneurship are the results of their immediate social and cultural environment.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to study a person tendencies or attitude is because human behavior is one of the major components which it can be judged and made decisions about the conduct or results (Akbari, Movahedi, & Kochekian, 2010). An investigation of pupils' attitudes towards entrepreneurs is important because these attitudes may reflect the prospect of becoming an entrepreneur themselves as a future career choice (Kolvereid, 1996;Guerrero et al, 2008).…”
Section: Introductionmentioning
confidence: 99%